Alien labors communities learning to cooperate to water pollution management of Tha Chin Basin - Thongphubate, Thanong; Yamabhai, Jitjayang (NIDA Development Journal, 2018)
Alien labors’ lifestyle makes traditional communities recognize that they do not feel bound local. They think that the management of water pollution in the community as something distant but do not feel responsible and not attend the event on managing water pollution. The traditional community recognizes that alien labors are the source of water pollution in the area. With local ties and love traditional community have a concern that alien labors increased rapidly to scramble for natural resources but lack of guardianship. The traditional community has to recognize the role and value to the management of water pollution, in very well and they can demonstrate active management of water pollution. In particular, the joint provision requirements, the draft budget, presentation of plans and project, control and resolve clearly, despite the lack of checks and balances. This study suggests: 1) there should be an organized community residents of alien labors, based on the cause of water pollution, the campaign, the cooperation, raising awareness by requiring labors to participate in the preparation of water pollution management plans. 2) Should provide for a review of the actual role comparable to that role should be to manage water pollution in traditional communities and alien labors and 3) Should adjust attitudes and local love values to the alien labors.